ISOLATION OF PROBIOTIC BACTERIAL CANDIDATES FROM the INTESTINE OF NILA (Oreochromis niloticus) TO CONTROL Streptococcus agalactiae - Sarbaini '; Iesje Lukistyowati; Nursyirwani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aim of this research was to isolate bacteria that had potential to act asprobiotics from the intestine to Oreochromis niloticus being cultured in RiauProvince; to investigate the optimum growth of at pH 2, 4 and 6; and to test theantibacterial potency of bacterial candidate probiotic against candidatepathogens Streptococcus agalactiae. The methods used in this research are Surveyand experiments methods were candidate in this research. Probiotic bacteria wasisolated from the inner wall of nila intestine. Twenty isolates were obtained fromfour fish. Identification based on physical, biochemical and morphologicalcharacters indicated that the isolates were classified into Bacillus andLactobacillus sp. Two of 20 isolate showed highest clear zone against S.agalactiae. They were isolate N-42 (22.7 mm), and N-62 (7.2 mm). Identificationby using API CHL 50 Kits identicated that the two isolates were chategorized intoLactobacillus paracasei spp NCFB with similirity of 82% dan 78%, respectivelyKey words: isolation, the bacteria candidates probiotics, Streptococcus agalactiae,Oreochromis niloticus